Content of Phenols and Flavonoids from Distillation of Beluntas (Pluchea indica l.) Leaves with Variables of Distillation Temperature and Pressure - Idiek Donowarti; Juli Rahaju; Djohar Noeriati Retno Dahoelat (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This study focuses on examining the properties of phenolic and flavonoid compounds that result from the distillation of beluntas (Pluchea indica L) leaves, with changes in temperature and distillation pressure as the variables.  A randomized block design method used in this reserach to arranged factorially with two factors, namely distillation temperature and distillation pressure. Data is displayed in the form of graphs and tables. The research results show that the variables of pressure and temperature of the distillation have a tendency to influence the bioactive levels of the distillation products analyzed. The pressure factor and increasing distillation temperature have a tendency to influence the levels of polyphenols and vitamin C, namely increasing the levels at a pressure of 14.5 psi, on the other hand reducing the levels of polyphenols and vitamin C at a pressure of 29 psi. Increasing distillation temperature does not tend to increase flavonoid levels at high pressure, while increasing two distillation factors, namely temperature and pressure, appears to increase the antioxidant capacity of distillation products.